Recycling spent lead acid batteries into aqueous zinc-ion battery material with ultra-flat voltage platforms. Issue 18 (15th September 2022) - Lin, Chun; Chen, Yue; Zhang, Weijian; Li, Jiaxin; Lin, Yingbin; Kolosov, Oleg V.; Huang, Zhigao
Abstract: The harmless disposal of lead paste in the spent lead-acid batteries (LABs) remains an enormous challenge in traditional pyrometallurgical recycling. Here, we introduced a hydrometallurgical method for the recycling of the spent LABs' waste to obtain the β -PbO as a novel zinc ion batteries (ZIBs) active material. The obtained β -PbO exhibits ultra-flat charge/discharge voltage platforms (0.21 mV/(mAh g −1 )) and stable specific capacity. During the charge/discharge, the β -PbO spontaneously triggers the formation of (ZnSO4 )[Zn(OH)2 ]3 ·5H2 O (ZHS) micro-sheets as a surface passivation layer. Moreover, the ex-situ X-ray spectra reveal that the reversible phase transformation occurs between PbSO4 and Pb with the assistance of ZHS by adjusting the PH value on the electrode-electrolyte interface. The synergistic two-phase-reaction mechanism generates ultra-flat voltage platforms upon the charge/discharge. This "energy-saving and environment-friendly" recycling route eliminates the major source of emission of pollution particulates/gases compared to the traditional pyrometallurgical recycling, while at the same time replacing energy-consuming and environmentally detrimental processes of synthesis of current ZIBs cathodes.